High-Q Split Ring Resonators for Tuning and Balun Applications - Lautenbacher, Thomas; Mzyk, Raphael; Weigel, Robert; Fischer, Georg; Kölpin, Alexander (Microwave and Radar Week MRW 2012 Warschau, 2012)
High-Q planar filters based on split ring resonators (SRRs) in suspended stripline technology (SSL) are investigated concerning different purposes. Initially, the SRR is analyzed regarding possibilities for optimization of quality factor Q. Beside this, the tuning potential of SRRs is explained. Therefore, an RF MEMS varactor is introduced together with an examination of its potential coupling methods to the SRR. Furthermore, the incorporation of the functionalities filter and balanced-to-unbalanced transformer (Balun) using one SRR is shown. The introduced concepts are proven by simulations and practical demonstrations.
elib2cris::1512001600,lautenbacher2012
Keywords: Split Ring Resonator; High-Q; Suspended Stripline; tuning; RF MEMS; varactor; balun; reconstruction filter

Klasse-E Leistungsverstärker mit Lastmodulation - Lautenbacher, Thomas; Schmidt, Christian; Fehr, Matthias; Kamper, Michael; Weigel, Robert; Fischer, Georg; Kölpin, Alexander (EEEfCOM 2012, 2012)
elib2cris::1512001600,lautenbacher2012a

Passive Metamaterial Structures for Use in Microwave and RF Applications - Fischer, Georg; Lautenbacher, Thomas; Kölpin, Alexander; Mzyk, Raphael; Weigel, Robert (ITG Topical Meeting New Microwave Materials, Non-Destructive Testing and Short-Range Imaging, Erlangen, 15. October 2009, 2009)
Possibilities for improving electrical system properties concerning size reduction, efficiency, multiband operation and tuning by using Metamaterial devices are presented. Two approaches in designing Metamaterial structures, i.e. the resonant type as well as the dual transmission line concept, are demonstrated by examples. With the dual transmission line concept, a dualband 90° Composite Right and Left Handed transmission line (CRLH TL) is implemented for use in dualband hybrid couplers and Wilkinson power dividers. Therefore new design guidelines for reliable functionality and superior performance were established for the stated implementation. The resonant type approach is based on resonant structures comprising of split ring resonators (SRR). Examples of using high-Q split ring resonators in duplex filters and in current switched class-S amplifiers are evaluated. Furthermore different aspects and possibilities in tuning SRRs by using MEMS devices are highlighted.
elib2cris::1512001600,fischer2009a
Keywords: Metamaterial; Composite Right and Left Handed CRLH; Dual Transmission Line Concept; Dualband; Hybrid Coupler; Wilkinson Power Divider; Split Ring Resonator SRR; High-Q; Duplex Filter; Class-S Amplifier; Tuning